Isotropic asphalt with excellent spinning performance as well as preparation method and application of isotropic asphalt

The preparation of isotropic asphalt with excellent spinning performance through low-temperature co-carbonization reaction and supercritical extraction processes has solved the problems of complex preparation methods, high cost and poor spinning performance in the prior art, and achieved efficient and low-cost improvement of the mechanical properties of carbon fibers.

CN119733448AActive Publication Date: 2025-04-01CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411792005.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-01
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The existing preparation methods of isotropic asphalt-based carbon fibers are complex in operation, high equipment requirements, high cost and poor spinning performance, which limit their large-scale application and market supply.

Method used

The co-carbonization reaction is controlled by low temperature and can condensate the aromatic molecules in the raw oil in shallow polycondensation, synthesize dimers linked by methylene, and use supercritical/subcritical extraction technology to achieve selective enrichment of dimers. Combined with fluidized bed tube reactors and flow control, the methylene bridge structure is "hered" into isotropic bitumen molecules, optimizing its structural composition and spatial configuration.

Benefits of technology

The continuous preparation of isotropic asphalt with excellent spinning performance is achieved. The operation process is relatively simple, the equipment requirements are not high, and the cost is low. The mechanical properties of carbon fiber are improved, and the tensile strength and tensile modulus are reached above 1.4GPa and above 51GPa.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119733448A_ABST
    Figure CN119733448A_ABST
Patent Text Reader

Abstract

The invention relates to isotropic asphalt with excellent spinning performance as well as a preparation method and application thereof, and belongs to the technical field of asphalt. The problems that in the prior art, a preparation method of isotropic pitch-based carbon fibers is relatively complex in operation process, high in equipment requirement, high in cost, poor in spinning performance and the like are solved. The preparation method comprises the following steps: firstly, by taking aromatic hydrocarbon-rich heavy oil as a raw material and polyaldehyde oxygen-containing macromolecules as a co-carbonization reagent, preparing low-polycondensation products with different molecular weights through co-carbonization reaction; then extracting the low-polycondensation product by using extracting agents with different solubility parameters by using a supercritical / subcritical extraction process to obtain a raffinate containing a dimer with the molecular weight of 330-450; and finally distilling the raffinate, recovering the extraction agent, carrying out thermal polycondensation treatment on the obtained dimer through a fluidized bed tubular reactor, and combining with flow control to obtain the isotropic asphalt. The isotropic asphalt has excellent spinning performance and can be used for preparing carbon fibers with excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an isotropic asphalt with excellent spinning performance and a preparation method and application thereof, in particular to the application of the isotropic asphalt in the preparation of carbon fiber, and belongs to the technical field of asphalt. Background Art

[0002] Asphalt-based carbon fiber is a fiber material with an ultra-high carbon content (>90%) and extremely excellent comprehensive performance. It has a series of excellent properties such as low density, high specific strength, high specific modulus, excellent extreme temperature resistance, outstanding corrosion resistance, fatigue resistance, creep resistance, high electrical conductivity, high thermal conductivity and small thermal expansion coefficient. It is widely used in aerospace, transportation, chemical industry, general engineering and other fields.

[0003] Asphalt-based carbon fiber can be divided into isotropic asphalt-based carbon fiber and mesophase asphalt-based carbon fiber. Among them, isotropic asphalt-based carbon fiber is prepared with isotropic asphalt as raw material, and is also called general-grade asphalt-based carbon fiber. Compared with mesophase asphalt-based carbon fiber, isotropic asphalt-based carbon fiber has huge market demand due to its advantages such as refined raw materials, simple process and low production cost. However, compared with foreign countries, my country's research and development time for asphalt-based carbon fiber is relatively short, and there is only one general-grade asphalt-based carbon fiber production line with an annual output of more than 200 tons, resulting in the current situation of low domestic production rate and insufficient supply in my country's asphalt-based carbon fiber market, which further restricts my country's economic and social development. Therefore, the development and production of high-strength isotropic asphalt-based carbon fiber is a major challenge facing my country's carbon fiber field.

[0004] Studies have found that the mechanical properties of carbon fibers are closely related to the molecular composition and spatial configuration of isotropic asphalt. Generally, the higher the linearity of the asphalt molecules, the better the spinning performance of the isotropic asphalt, and the higher the mechanical properties of the corresponding carbon fibers. This is because during the melt spinning process, under the influence of shear force, the asphalt molecules with high linearity are more likely to be oriented inside the carbon fibers, resulting in improved mechanical properties of the resulting carbon fibers. In order to improve the linearity of the asphalt molecules, people introduce methylene bridging structures into the asphalt molecules through bromination-debromination. This method has significant effects, but the operation process of this method is relatively complex and has high requirements for equipment. Liquid bromine is highly corrosive, and the reaction produces by-products such as HBr. If the operation is improper, it will seriously pollute the environment, limiting the large-scale application of the process. In addition, the complex production process further increases the production cost of isotropic asphalt-based carbon fibers.

[0005] CN115466626B provides a method for preparing high-quality isotropic pitch, which first adds methylnaphthalene and a brominating agent to a solvent, performs a bromination reaction under visible light catalysis, obtains brominated methylnaphthalene, then mixes it with coal tar pitch, performs a co-carbonization reaction under an inert gas atmosphere, obtains the high-quality isotropic pitch, and uses it as a raw material to prepare carbon fiber. This method solves the problem of low reactivity of coal tar pitch to a certain extent, but involves the use of liquid bromine, a highly corrosive reagent, requires special production equipment, and has a low yield of isotropic pitch, resulting in increased production costs.

[0006] CN115873617A discloses a method for preparing petroleum-based isotropic high softening point asphalt. First, the petroleum-based aromatic-rich raw oil is enriched with a fraction of 250-350°C by nitrogen purge at a certain temperature, and then the temperature is raised to 400-420°C for reaction for 13 hours to obtain a high softening point isotropic asphalt. However, the degree of polycondensation of the asphalt molecules prepared by this method is relatively high, resulting in an increase in the content of quinoline insolubles and a decrease in the asphalt spinning performance.

[0007] CN116288816A provides a method for preparing isotropic asphalt-based carbon fibers. The method uses ethylene tar as a raw material, first heat-treats it in a nitrogen atmosphere, then mixes it with coal tar and simultaneously introduces nitrogen bromosuccinimide, and irradiates it with a xenon lamp at a certain temperature and removes benzene to obtain isotropic asphalt. However, the method has a complex process route, a high production cost, and the resulting asphalt has a high softening point and poor spinning performance. Summary of the invention

[0008] In view of this, the present invention provides an isotropic asphalt with excellent spinning performance and its preparation method and application in order to solve the technical problems in the prior art such as relatively complex operation process, high equipment requirements, high cost, and poor spinning performance of the preparation method of isotropic asphalt-based carbon fiber.

[0009] The present invention uses a low-temperature controllable induced co-carbonization reaction to shallowly polycondense the aromatic molecules in the crude oil to synthesize dimers linked by methylene groups, and uses a supercritical / subcritical extraction process to achieve selective enrichment of the dimer. Then, a fluidized bed tubular reactor is used in combination with flow control to promote further polymerization of the dimer and "inherit" the methylene bridging structure into the isotropic asphalt molecule. This method achieves the purpose of simultaneously improving the asphalt spinning performance and the carbon fiber mechanical properties by optimizing the structural composition and spatial configuration of the asphalt molecules.

[0010] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is as follows.

[0011] The present invention provides a method for continuously preparing isotropic pitch with excellent spinning performance, comprising the following steps:

[0012] (1) Using aromatic-rich heavy oil as raw material and polyaldehyde oxygen-containing polymer as co-carbonization reagent, the reaction parameters are adjusted to prepare low-molecular-weight polycondensation products with different molecular weights through co-carbonization reaction;

[0013] (2) using a supercritical / subcritical extraction process, selecting extractants with different solubility parameters to extract the low polycondensation product prepared in step (1), and adjusting the extraction parameters to obtain an extract containing a dimer with a molecular weight of 330-450;

[0014] (3) distilling the extract prepared in step (2) to recover the extractant, and subjecting the obtained dimer to thermal polycondensation through a fluidized bed tubular reactor, and combining the flow rate control of the dimer to prepare linear polycyclic aromatic hydrocarbon macromolecules with a molecular weight of 820-1130 and a softening point of 250-290°C, thereby obtaining isotropic asphalt.

[0015] Preferably, in step (1), the aromatics-rich heavy oil is one or more of catalytic cracking slurry, ethylene tar, atmospheric residue oil, vacuum residue oil, high-temperature coal tar, and bamboo tar.

[0016] Preferably, in step (1), the co-carbonization agent is one or more of trioxymethylene, pentamethylene, and polyacetaldehyde; more preferably, the co-carbonization agent is trioxymethylene.

[0017] Preferably, in step (1), the amount of the co-carbonization agent used is 3wt%-10wt% of the mass of the aromatics-rich heavy oil.

[0018] Preferably, in step (1), the reaction temperature of the co-carbonization is 160-200° C., and the reaction time is 0.5-1.5 h; more preferably, the reaction temperature of the co-carbonization is 180° C., and the reaction time is 1.1 h.

[0019] Preferably, in step (1), the molecular weight of the oligocondensation product is in the range of 100-550.

[0020] Preferably, in step (2), the equipment used in the supercritical / subcritical extraction process is a supercritical extraction tower, the tower top temperature is 400-430°C, the tower temperature is 370-390°C, the tower bottom temperature is 310-370°C, the extraction pressure is 1.6-3.2MPa, the extractant is selected from one or more of toluene, N-methylpyrrolidone, chloroform, carbon tetrachloride, furfural, tetrahydrofuran, and the mass ratio of the extractant to the low polycondensation product (agent-to-oil ratio) is 5:1-9:1;

[0021] More preferably, the tower top temperature is 425°C, the tower temperature is 381°C, the tower bottom temperature is 330°C, and the extraction pressure is 2.2MPa;

[0022] More preferably, the extractant is a mixed solvent of toluene, furfural and chloroform in a mass ratio of 1:1:4;

[0023] More preferably, the extractant and the oligocondensation product are mixed in a countercurrent manner.

[0024] Preferably, in step (2), the methylene carbon content (C CH2 )≥15wt%, aromatic content≥75wt%, asphaltene content≤4wt%, ash content≤5μg / g.

[0025] Preferably, in step (3), the distillation temperature is 160-210°C, and the pressure is -20KPa to -40KPa; more preferably, the distillation temperature is 200°C, and the pressure is -30KPa.

[0026] Preferably, in step (3), the fluidized bed tubular reactor is divided into three temperature zones, the treatment temperature in the first temperature zone is 220-270°C, the treatment temperature in the second temperature zone is 300-340°C, and the treatment temperature in the third temperature zone is 350-380°C.

[0027] Preferably, in step (3), the flow rate of the dimer is 20-50 ml / min.

[0028] Preferably, in step (3), the methylene carbon content (C CH2 )≥11wt%.

[0029] The present invention also provides isotropic asphalt prepared by the above-mentioned continuous preparation method of isotropic asphalt.

[0030] The present invention also provides application of the isotropic asphalt in preparing carbon fiber.

[0031] Preferably, the isotropic pitch is subjected to melt spinning, pre-oxidation and carbonization treatment to obtain carbon fibers.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] The continuous preparation method of isotropic asphalt with excellent spinning performance of the present invention uses aromatic-rich heavy oil as raw material and the thermal decomposition product of polyaldehyde oxygen-containing polymer as cross-linking agent. The aromatic components in the aromatic-rich heavy oil are linked together through a methylene bridge structure by co-carbonization reaction at low temperature to form dimers with a shallow degree of polycondensation. This structure can not only improve the solubility of the polycondensation product, making it easy to efficiently enrich it in the subsequent supercritical / subcritical extraction process, but also the methylene bridge structure will be "inherited" to the inside of the isotropic asphalt molecule, improving the linearity of the asphalt molecule, thereby enhancing the spinnability of the asphalt. In addition, in the supercritical / subcritical extraction process, by adjusting the extraction parameters of the supercritical extraction tower, while ensuring the efficient enrichment of the dimers in the polycondensation product, the unreacted raw material components can also be removed and re-enter the reaction system as raw materials, thereby improving the utilization rate of the raw materials. In order to allow more methylene bridging structures to enter the asphalt molecules, a multi-temperature zone fluidized bed tubular reactor is used to further condense the dimer to form polycyclic aromatic hydrocarbon molecules with higher molecular weight. This multi-temperature zone fluidized bed tubular reactor not only increases the reaction rate, but also better preserves the methylene bridging structure in the dimer, thereby improving the linearity of the asphalt molecules.

[0034] The continuous preparation method of isotropic asphalt with excellent spinning performance of the present invention has relatively simple operation process, low requirements on equipment and low cost.

[0035] The isotropic asphalt with excellent spinning performance of the present invention is easily oriented inside the fiber under the influence of shear force during the melt spinning process, thereby reducing the number of microscopic defects and improving the mechanical properties of the carbon fiber. According to the test, the tensile strength of the carbon fiber is ≥1.4GPa and the tensile modulus is ≥50GPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the technical solutions in the specific implementation modes of the present invention, the drawings required for use in the specific implementation modes will be briefly introduced below. Obviously, the drawings described below are only some specific implementation modes of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0037] Figure 1 A schematic diagram of the process flow of the continuous preparation method of isotropic asphalt with excellent spinning performance provided by the present invention. DETAILED DESCRIPTION

[0038] In order to further understand the present invention, preferred embodiments of the present invention are described below. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0039] The continuous preparation method of isotropic pitch with excellent spinning performance of the present invention comprises the following steps:

[0040] (1) Using aromatic-rich heavy oil as raw material and polyaldehyde oxygen-containing polymer as co-carbonization reagent, the reaction parameters are adjusted, and the aromatic molecules in the aromatic-rich heavy oil are connected through a methylene bridge structure through a low-temperature controllable induced co-carbonization reaction to obtain low-molecular-weight polycondensation products with different molecular weights;

[0041] (2) using a supercritical / subcritical extraction process, selecting extractants with different solubility parameters to extract the low polycondensation product prepared in step (1), and adjusting the extraction parameters to obtain a raffinate containing dimers with a molecular weight of 330-450, and the extracted light distillate oil can be discharged and stored;

[0042] (3) distilling the extract prepared in step (2) to recover the extractant, and subjecting the obtained dimer to thermal polycondensation through a fluidized bed tubular reactor, and combining the flow rate control of the dimer to prepare linear polycyclic aromatic hydrocarbon macromolecules with a molecular weight of 820-1130 and a softening point of 250-290°C, thereby obtaining isotropic asphalt.

[0043] In the present invention, the aromatic-rich heavy oil is preferably one or more of catalytic cracking oil, ethylene tar, atmospheric residue, vacuum residue, high-temperature coal tar, and bamboo tar. The co-carbonization agent is preferably one or more of trioxymethylene, pentamethylene, and polyacetaldehyde, and is more preferably trioxymethylene. The amount of the co-carbonization agent is preferably 3wt%-10wt% of the mass of the aromatic-rich heavy oil. The co-carbonization reaction temperature is preferably 160-200°C, and the reaction time is 0.5-1.5h; more preferably, the co-carbonization reaction temperature is 180°C, and the reaction time is 1.1h. The molecular weight range of the preferred low polycondensation product is 100-550, usually measured by gel permeation chromatography.

[0044] In the present invention, the equipment used in the supercritical / subcritical extraction process is preferably a supercritical extraction tower, the tower top temperature is 400-430°C, the tower temperature is 370-390°C, the tower bottom temperature is 310-370°C, the extraction pressure is 1.6-3.2MPa, preferably the tower top temperature is 425°C, the tower temperature is 381°C, the tower bottom temperature is 330°C, and the extraction pressure is 2.2MPa. The extractant is selected from one or more of toluene, N-methylpyrrolidone, chloroform, carbon tetrachloride, furfural, and tetrahydrofuran; the preferred extractant is a mixed solvent of toluene, furfural and chloroform in a mass ratio of 1:1:4. The mass ratio (agent-oil ratio) of the extractant and the low polycondensation product is 5:1-9:1. The extractant and the low polycondensation product are preferably mixed in a countercurrent manner.

[0045] In the present invention, the distillation is preferably flash distillation, the distillation temperature is 160-210°C, the pressure is -20KPa to -40KPa, preferably 200°C, the pressure is -30KPa. 13 C-NMR analysis determined the methylene carbon content (C CH2 )≥15wt%, the aromatic content in the dimer measured by four-component analysis is ≥75wt%, the asphaltene content is ≤4wt%, and the ash content is ≤5μg / g. The preferred fluidized bed tubular reactor is divided into three temperature zones, the first temperature zone treatment temperature is 220-270℃, the second temperature zone treatment temperature is 300-340℃, and the third temperature zone treatment temperature is 350-380℃. The preferred dimer flow rate is 20-50ml / min. 13 C-NMR analysis was used to determine the methylene carbon content (C CH2 )≥11wt%.

[0046] like Figure 1 As shown, as a preferred embodiment, the continuous preparation method of isotropic asphalt with excellent spinning performance of the present invention is described in combination with the device, and the steps are as follows: first, the aromatic-rich heavy oil in the raw oil storage tank is transported to the reactor through a pipeline pump and a heat exchanger, and at the same time, the co-carbonization reagent stored in the cross-linking agent storage tank is transported to the reactor, and the reaction parameters are regulated. The aromatic molecules in the aromatic-rich heavy oil are connected through a methylene bridge structure through a low-temperature controllable induced co-carbonization reaction to obtain low-polycondensation products with different molecular weights; the low-polycondensation products enter the supercritical extraction tower after passing through a pipeline metering pump and a heat exchanger, and at the same time, the extractant in the extract storage tank is transported through a pipeline pump to the reactor. It is sent to a supercritical extraction tower, where the extractant contacts the low polycondensation product, and a light fraction oil is obtained at the top of the tower, which is transported to a light fraction oil receiving tank for storage. A residue containing dimers with a molecular weight of 330-450 is obtained at the bottom of the tower, which is discharged and sent to a dimer storage tank. The residue in the dimer storage tank is first transported to a flash tower for flash evaporation via a heat exchanger and a pipeline pump, and the extractant is recovered and transported to a recovery extractant storage tank via a vacuum pump, and then can be transported to an extractant storage tank for reuse. The enriched dimer is transported to a fluidized bed tubular reactor via a pipeline metering pump, and the dimer is subjected to a thermal polycondensation treatment to obtain isotropic asphalt, which is stored in an isotropic asphalt storage tank. It should be noted that the above device is only for a clearer description of the preparation method of the present invention, and those skilled in the art can select other devices suitable for the preparation method of the present invention as needed.

[0047] The isotropic asphalt of the present invention can be used in the preparation of carbon fiber. There is no special limitation on the specific application method, and reference can be made to the method for preparing carbon fiber from asphalt in the prior art, which mainly includes subjecting the isotropic asphalt to melt spinning, pre-oxidation, and carbonization treatment to obtain carbon fiber. Preferably, the carbon fiber precursor is obtained by melt spinning in a nitrogen atmosphere at 305°C-335°C, and then pre-oxidation treatment is carried out in an air (50ml / min) atmosphere at 275°C, and then carbonization treatment is carried out in a nitrogen (100ml / min) atmosphere at 1100°C to obtain the carbon fiber. Since the isotropic asphalt of the present invention has an excellent spatial configuration, the carbon fiber prepared therefrom has excellent tensile properties.

[0048] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below in conjunction with embodiments.

[0049] In the following examples, various processes and methods not described in detail are conventional methods known in the art. Unless otherwise specified, the materials, reagents, devices, instruments, equipment, etc. used in the following examples can be obtained from commercial sources.

[0050] Example 1

[0051] Weigh 2kg of catalytic cracking oil slurry, transport it to the reactor by pipeline pump, add 100g of trioxymethylene into the reactor, react at 160℃ for 1.1h, then transport the reaction product to a supercritical extraction tower, set the tower top temperature to 425℃, the tower temperature to 381℃, the tower bottom temperature to 330℃, the extraction pressure to 2.2MPa, and select a mixed solvent of toluene, furfural and chloroform with a mass ratio of 1:1:4 as the extractant, the mass ratio of the extractant to the reaction product (agent-to-oil ratio) to 7:1, then transport the residue containing dimers to a flash tank to recover the extractant, set the flash temperature to 425℃, the tower top temperature to 381℃, the tower bottom temperature to 330℃, the extraction pressure to 2.2MPa, and select a mixed solvent of toluene, furfural and chloroform with a mass ratio of 1:1:4 as the extractant, the mass ratio of the extractant to the reaction product to 7:1, then transport the residue containing dimers to a flash tank to recover the extractant, set the flash temperature to 425℃, the tower top temperature to 381℃, the tower bottom temperature to 330℃, the extraction pressure to 2.2MPa, and set the tower top temperature to 425℃, the tower middle ... set the tower top temperature to 425℃, the tower middle temperature to 381℃, the tower bottom temperature to 33 The temperature is 200°C and the pressure is -30KPa. The enriched dimer is transported to the fluidized bed tubular reactor by a pipeline metering pump. The treatment temperature in the first temperature zone is 250°C, the treatment temperature in the second temperature zone is 310°C, and the treatment temperature in the third temperature zone is 370°C. The flow rate of the dimer is controlled at 41ml / min to obtain isotropic asphalt, and then melt-spun in a nitrogen atmosphere at 305°C to obtain carbon fiber precursor, which is pre-oxidized in air (50ml / min) atmosphere at 275°C and then carbonized in a nitrogen atmosphere (100ml / min) at 1100°C to obtain carbon fiber.

[0052] The test found that the weight average molecular weight of the dimer enriched after supercritical extraction was 337. 13 C-NMR analysis determined the methylene carbon content (C CH2)15.2wt%, four-component analysis showed that the aromatic content was 83wt%, the asphaltene content was 3.6wt%, and the ash content was 4μg / g. The weight average molecular weight of the obtained isotropic asphalt was 846, and the softening point was 255℃. 13 C-NMR analysis was used to determine the methylene carbon content in asphalt. CH2 )14.1wt%, the obtained carbon fiber has a tensile strength of 1.4GPa and a tensile modulus of 51GPa.

[0053] Example 2

[0054] Weigh 2kg of catalytic cracking oil slurry, transport it to the reactor by pipeline pump, add 100g of polyacetaldehyde into the reactor, react at 200℃ for 1.1h, then transport the reaction product to a supercritical extraction tower, set the tower top temperature to 425℃, the tower temperature to 381℃, the tower bottom temperature to 330℃, the extraction pressure to 2.2MPa, and select a mixed solvent of toluene, furfural and chloroform in a mass ratio of 1:1:4 as the extractant, the mass ratio of the extractant to the reaction product (agent-to-oil ratio) to 7:1, then transport the residue containing dimers to a flash tank to recover the extractant, set the flash temperature to 425℃, the tower top temperature to 381℃, the tower bottom temperature to 330℃, the extraction pressure to 2.2MPa, and select a mixed solvent of toluene, furfural and chloroform in a mass ratio of 1:1:4 as the extractant, the mass ratio of the extractant to the reaction product to 7:1, then transport the residue containing dimers to a flash tank to recover the extractant, set the flash temperature to 425℃, the tower top temperature to 381℃, the tower bottom temperature to 330℃, the extraction pressure to 2.2MPa, and set the tower top temperature to 425℃, the tower middle ... set the tower top temperature to 425℃, the tower middle temperature to 381℃, the tower bottom temperature to 33 The temperature is 200°C and the pressure is -30KPa. The enriched dimer is transported to the fluidized bed tubular reactor by a pipeline metering pump. The treatment temperature in the first temperature zone is 250°C, the treatment temperature in the second temperature zone is 310°C, and the treatment temperature in the third temperature zone is 370°C. The flow rate of the dimer is controlled at 41ml / min to obtain isotropic asphalt, and then melt-spun in a nitrogen atmosphere at 317°C to obtain carbon fiber precursor, which is pre-oxidized in air (50ml / min) atmosphere at 275°C and then carbonized in a nitrogen atmosphere (100ml / min) at 1100°C to obtain carbon fiber.

[0055] The test found that the weight average molecular weight of the dimer enriched after supercritical extraction was 336. 13 C-NMR analysis determined the methylene carbon content (C CH2 )16.3wt%, four-component analysis showed that the aromatic content was 78wt%, the asphaltene content was 3.7wt%, and the ash content was 4.6μg / g. The weight average molecular weight of the obtained isotropic asphalt was 874, and the softening point was 267℃. 13 C-NMR analysis was used to determine the methylene carbon content in asphalt. CH2 )11.1wt%, the obtained carbon fiber has a tensile strength of 1.43GPa and a tensile modulus of 57GPa.

[0056] Example 3

[0057] Weigh 2kg of catalytic cracking oil slurry, use a pipeline pump to transport it to the reactor, and add 100g of trioxymethylene into the reactor, react at 180°C for 1.1h, then transport the reaction product to a supercritical extraction tower, set the tower top temperature to 425°C, the tower temperature to 381°C, the tower bottom temperature to 330°C, the extraction pressure to 2.2MPa, and select a mixed solvent of toluene, furfural and chloroform in a mass ratio of 1:1:4 as the extractant, the mass ratio of the extractant to the reaction product (agent-to-oil ratio) is 7:1, then transport the residue containing dimers to a flash tank to recover the extractant, set the flash tank to extract the dimer, and then transport the residue to a flash tank to recover the extractant. The temperature is 200°C and the pressure is -30KPa. The enriched dimer is transported to the fluidized bed tubular reactor by a pipeline metering pump. The treatment temperature in the first temperature zone is set to 250°C, the treatment temperature in the second temperature zone is set to 310°C, and the treatment temperature in the third temperature zone is set to 370°C. The flow rate of the dimer is controlled to be 41ml / min to obtain isotropic asphalt, and then melt-spinning is performed in a nitrogen atmosphere at 315°C to obtain carbon fiber precursor, which is pre-oxidized in an air (50ml / min) atmosphere at 275°C and then carbonized in a nitrogen atmosphere (100ml / min) at 1100°C to obtain carbon fiber.

[0058] The test found that the weight average molecular weight of the dimer enriched after supercritical extraction was 386. 13 C-NMR analysis determined the methylene carbon content (C CH2 )17.2wt%, four-component analysis showed that the aromatic content was 88wt%, the asphaltene content was 2.4wt%, and the ash content was 1.7μg / g. The weight average molecular weight of the obtained isotropic asphalt was 983, and the softening point was 265℃. 13 C-NMR analysis was used to determine the methylene carbon content in asphalt. CH2 )13.4wt%, the obtained carbon fiber has a tensile strength of 1.7GPa and a tensile modulus of 67GPa.

[0059] Example 4

[0060] Weigh 2kg of catalytic cracking oil slurry, use a pipeline pump to transport it to the reactor, and add 100g of trioxymethylene into the reactor, react at 180°C for 1.1h, then transport the reaction product to a supercritical extraction tower, set the tower top temperature to 425°C, the tower temperature to 381°C, the tower bottom temperature to 330°C, the extraction pressure to 2.2MPa, and select a mixed solvent of toluene, furfural and chloroform in a mass ratio of 1:1:4 as the extractant, the mass ratio of the extractant to the reaction product (agent-to-oil ratio) is 7:1, then transport the residue containing dimers to a flash tank to recover the extractant, set the flash tank to extract the dimer, and then transport the residue to a flash tank to recover the extractant. The temperature is 200°C and the pressure is -30KPa. The enriched dimer is transported to the fluidized bed tubular reactor by a pipeline metering pump. The treatment temperature in the first temperature zone is set to 250°C, the treatment temperature in the second temperature zone is set to 310°C, and the treatment temperature in the third temperature zone is set to 370°C. The flow rate of the dimer is controlled to be 41ml / min to obtain isotropic asphalt, and then melt-spun in a nitrogen atmosphere at 305°C to obtain carbon fiber precursor, which is pre-oxidized in an air (50ml / min) atmosphere at 275°C and then carbonized in a nitrogen (100ml / min) atmosphere at 1100°C to obtain carbon fiber.

[0061] The test found that the weight average molecular weight of the dimer enriched after supercritical extraction was 391. 13 C-NMR analysis determined the methylene carbon content (C CH2 )15.2wt%, four-component analysis showed that the aromatic content was 79wt%, the asphaltene content was 3.4wt%, and the ash content was 3.7μg / g. The weight average molecular weight of the obtained isotropic asphalt was 963, and the softening point was 255℃. 13 C-NMR analysis was used to determine the methylene carbon content in asphalt. CH2 )15.4wt%, the obtained carbon fiber has a tensile strength of 1.55GPa and a tensile modulus of 56GPa.

[0062] Example 5

[0063] Weigh 2kg of ethylene tar and transport it to the reactor using a pipeline pump. Add 100g of trioxymethylene into the reactor and react at 180°C for 1.1h. Then transport the reaction product to a supercritical extraction tower. Set the top temperature of the tower to 425°C, the temperature in the tower to 381°C, the bottom temperature to 330°C, and the extraction pressure to 2.2MPa. At the same time, a mixed solvent of toluene, furfural and chloroform in a mass ratio of 1:1:4 is selected as the extractant. The mass ratio of the extractant to the reaction product (agent-to-oil ratio) is 7:1. Then, the residue containing the dimer is transported to a flash tank to recover the extractant. Set the flash temperature to 425°C, the temperature in the tower to 381°C, the temperature at the bottom to 330°C, and the extraction pressure to 2.2MPa. The temperature is 200°C and the pressure is -30KPa. The enriched dimer is transported to the fluidized bed tubular reactor by a pipeline metering pump. The treatment temperature in the first temperature zone is 250°C, the treatment temperature in the second temperature zone is 310°C, and the treatment temperature in the third temperature zone is 370°C. The flow rate of the dimer is controlled at 41ml / min to obtain isotropic asphalt, and then melt-spun in a nitrogen atmosphere at 312°C to obtain carbon fiber precursor, which is pre-oxidized in air (50ml / min) atmosphere at 275°C and then carbonized in a nitrogen atmosphere (100ml / min) at 1100°C to obtain carbon fiber.

[0064] The test found that the weight average molecular weight of the dimer enriched after supercritical extraction was 367. 13 C-NMR analysis determined the methylene carbon content (C CH2 )16.2wt%, four-component analysis showed that the aromatic content was 89wt%, the asphaltene content was 2.1wt%, and the ash content was 1.1μg / g. The weight average molecular weight of the obtained isotropic asphalt was 917, and the softening point was 262℃. 13 C-NMR analysis was used to determine the methylene carbon content in asphalt. CH2 )14.4wt%, the obtained carbon fiber has a tensile strength of 1.67GPa and a tensile modulus of 62GPa.

[0065] Example 6

[0066] Weigh 2kg of vacuum residue oil, transport it to the reactor by pipeline pump, add 100g of trioxymethylene into the reactor, react at 180℃ for 1.1h, then transport the reaction product to a supercritical extraction tower, set the top temperature of the tower to 425℃, the temperature in the tower to 381℃, the bottom temperature of the tower to 330℃, the extraction pressure to 2.2MPa, and select a mixed solvent of toluene, furfural and chloroform in a mass ratio of 1:1:4 as the extractant, the mass ratio of the extractant to the reaction product (agent-to-oil ratio) is 7:1, then transport the residue containing dimers to a flash tank to recover the extractant, set the flash temperature to 425℃, the temperature in the tower to 381℃, the temperature at the bottom of the tower to 330℃, the extraction pressure to 2.2MPa, and select a mixed solvent of toluene, furfural and chloroform in a mass ratio of 1:1:4 as the extractant, the mass ratio of the extractant to the reaction product (agent-to-oil ratio) is 7:1, and then transport the residue containing dimers to a flash tank to recover the extractant, set the flash temperature to 425℃, the temperature in the tower to 381℃, the bottom temperature to 330℃, the extraction pressure to 2.2MPa ... reaction product to a supercritical extraction tower, set the top temperature to 425℃, the temperature in the tower to The temperature is 200°C and the pressure is -30KPa. The enriched dimer is transported to the fluidized bed tubular reactor by a pipeline metering pump. The treatment temperature in the first temperature zone is 250°C, the treatment temperature in the second temperature zone is 310°C, and the treatment temperature in the third temperature zone is 370°C. The flow rate of the dimer is controlled at 41ml / min to obtain isotropic asphalt, and then melt-spun in a nitrogen atmosphere at 335°C to obtain carbon fiber precursor, which is pre-oxidized in air (50ml / min) atmosphere at 275°C and then carbonized in a nitrogen atmosphere (100ml / min) at 1100°C to obtain carbon fiber.

[0067] The test found that the weight average molecular weight of the dimer enriched after supercritical extraction was 374. 13 C-NMR analysis determined the methylene carbon content (C CH2 )15.7wt%, four-component analysis showed that the aromatic content was 82wt%, the asphaltene content was 3.9wt%, and the ash content was 2.7μg / g. The weight average molecular weight of the obtained isotropic asphalt was 924, and the softening point was 281℃. 13 C-NMR analysis was used to determine the methylene carbon content in asphalt. CH2 )15.4wt%, the obtained carbon fiber has a tensile strength of 1.57GPa and a tensile modulus of 57GPa.

[0068] Comparative Example 1

[0069] Weigh 2 kg of catalytic cracking oil slurry, transport it to the reactor by a pipeline pump, heat it at 180°C for 1.1 h, and then transport the obtained reaction product to a fluidized bed tubular reactor by a pipeline metering pump. Set the treatment temperature in the first temperature zone to 250°C, the treatment temperature in the second temperature zone to 310°C, and the treatment temperature in the third temperature zone to 370°C. Control the flow rate of the reaction product at 41 ml / min to obtain asphalt, and then melt-spin it at 285°C in a nitrogen atmosphere to obtain carbon fiber precursor, pre-oxidize it at 275°C in an air (50 ml / min) atmosphere, and then carbonize it at 1100°C in a nitrogen (100 ml / min) atmosphere to obtain carbon fiber.

[0070] The test found that the weight average molecular weight of the obtained asphalt was 669 and the softening point was 215℃. 13 C-NMR analysis determined the methylene carbon content in asphalt. CH2 )1.1wt%, the obtained carbon fiber has a tensile strength of 0.28GPa and a tensile modulus of 15GPa.

[0071] Comparative Example 2

[0072] Weigh 2 kg of catalytic cracking oil slurry, transport it to the reactor by pipeline pump, heat it at 180 ° C for 1.1 h, and then transport the obtained reaction product to the supercritical extraction tower by pipeline metering pump, set the tower top temperature to 425 ° C, the tower temperature to 381 ° C, the tower bottom temperature to 330 ° C, the extraction pressure to 2.2 MPa, and select a mixed solvent of toluene, furfural and chloroform with a mass ratio of 1:1:4 as the extractant, and the mass ratio of the extractant to the reaction product (agent-oil ratio) is 7:1. Then the residue is transported to the flash tank to recover the extractant, and the flash temperature is set to 20 0℃, pressure is -30KPa, the enriched dimer is transported to the fluidized bed tubular reactor by a pipeline metering pump, the treatment temperature of the first temperature zone is set to 250℃, the treatment temperature of the second temperature zone is set to 310℃, the treatment temperature of the third temperature zone is set to 370℃, the flow rate of the dimer is controlled to 41ml / min, asphalt is obtained, and then melt-spinning is carried out at 295℃ in a nitrogen atmosphere to obtain carbon fiber precursor, which is pre-oxidized at 275℃ in an air (50ml / min) atmosphere, and then carbonized at 1100℃ in a nitrogen atmosphere (100ml / min) to obtain carbon fiber.

[0073] The test found that the weight average molecular weight of the dimer enriched by supercritical extraction was 331. 13 C-NMR analysis determined the methylene carbon content (C CH2 )3.2wt%, four-component analysis showed that the aromatic content was 85wt%, the asphaltene content was 18wt%, and the ash content was 9μg / g. The weight average molecular weight of the obtained asphalt was 916, and the softening point was 231℃. 13 C-NMR analysis measured the methylene carbon content of asphalt (C CH2 )2.1wt%, the tensile strength of the obtained carbon fiber is 0.3GPa and the tensile modulus is 18GPa.

[0074] Obviously, the above embodiments are merely examples for clear explanation, and are not intended to limit the embodiments. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. The obvious changes or modifications derived from them are still within the protection scope of the invention.

Claims

1. A continuous preparation method for isotropic asphalt, characterized in that: The steps include: (1) Using aromatic-rich heavy oil as raw material and polyaldehyde oxygen-containing polymer as co-carbonization reagent, the reaction parameters are adjusted to prepare low-molecular-weight polycondensation products with different molecular weights through co-carbonization reaction; (2) using a supercritical / subcritical extraction process, selecting extractants with different solubility parameters to extract the low polycondensation product prepared in step (1), and adjusting the extraction parameters to obtain an extract containing a dimer with a molecular weight of 330-450; (3) distilling the extract prepared in step (2) to recover the extractant, and subjecting the obtained dimer to thermal polycondensation through a fluidized bed tubular reactor, and combining the flow rate control of the dimer to prepare linear polycyclic aromatic hydrocarbon macromolecules with a molecular weight of 820-1130 and a softening point of 250-290°C, thereby obtaining isotropic asphalt.

2. The continuous preparation method of isotropic asphalt according to claim 1, characterized in that: In step (1), the aromatics-rich heavy oil is one or more of catalytic cracking slurry, ethylene tar, atmospheric residue, vacuum residue, high-temperature coal tar, and bamboo tar; And / or, the co-carbonization agent is one or more of trioxymethylene, pentamethylene, and polyacetaldehyde; And / or, the amount of the co-carbonization agent used is 3wt%-10wt% of the mass of the aromatics-rich heavy oil.

3. The continuous preparation method of isotropic asphalt according to claim 1, characterized in that: In step (1), the reaction temperature of the co-carbonization is 160-200° C., the reaction time is 0.5-1.5 h, and the molecular weight range of the low polycondensation product is 100-550.

4. The continuous preparation method of isotropic asphalt according to claim 1, characterized in that: In step (2), the equipment used in the supercritical / subcritical extraction process is a supercritical extraction tower, the tower top temperature is 400-430°C, the tower temperature is 370-390°C, the tower bottom temperature is 310-370°C, and the extraction pressure is 1.6-3.2MPa; the extractant is selected from one or more of toluene, N-methylpyrrolidone, chloroform, carbon tetrachloride, furfural, and tetrahydrofuran, and the mass ratio of the extractant to the low polycondensation product is 5:1-9:

1.

5. The continuous preparation method of isotropic asphalt according to claim 4, characterized in that: The extractant and the low polycondensation product are mixed in a countercurrent manner; And / or, the extractant is a mixed solvent of toluene, furfural and chloroform in a mass ratio of 1:1:4; And / or, the tower top temperature is 425° C., the tower middle temperature is 381° C., the tower bottom temperature is 330° C., and the extraction pressure is 2.2 MPa.

6. The continuous preparation method of isotropic asphalt according to claim 1, characterized in that: In step (3), the distillation temperature is 160-210° C. and the pressure is -20 KPa to -40 KPa; And / or, the fluidized bed tubular reactor is divided into three temperature zones, the treatment temperature in the first temperature zone is 220-270°C, the treatment temperature in the second temperature zone is 300-340°C, and the treatment temperature in the third temperature zone is 350-380°C; And / or, the flow rate of the dimer is 20-50 ml / min.

7. The continuous preparation method of isotropic asphalt according to claim 1, characterized in that: In step (3), the dimer has a methylene carbon content of ≥15wt%, an aromatic content of ≥75wt%, an asphaltene content of ≤4wt%, and an ash content of ≤5μg / g; And / or, the methylene carbon content in the isotropic asphalt is ≥ 11 wt%.

8. Isotropic asphalt prepared by the continuous preparation method according to any one of claims 1 to 7.

9. Use of the isotropic pitch according to claim 8 in the preparation of carbon fiber.

10. The use of the isotropic pitch in the preparation of carbon fiber according to claim 9, characterized in that: The isotropic pitch is subjected to melt spinning, pre-oxidation and carbonization treatment to obtain carbon fiber.

Citation Information

Patent Citations

  • Method for simultaneously producing mesophase pitch and COPNA resin from heavy oil

    CN118185652A

  • Method for preparing isotropic pitch-based carbon fiber by introducing biomass

    CN118326568A

  • Molding material, electrical / Electronic part material and semiconductor sealing medium which contain highly reactive modified phenolic resin and epoxy resin

    JP2002332322A

  • Carbon black, a process for preparation thereof and use thereof

    US20110076608A1

  • Method for preparing bitumen solid at ambient temperature, in a fluidised air bed

    US20200247011A1